Nonlinear Response of Loaded Drivetrain Gear Rattle - Wang Xinchao; Hu Xiaobing; Zhang Bingbing; Jiang Shuxin (Jixie chuandong)
The lightly loaded or unloaded gears rattle in vehicle transmission systems is an unsolved issue for vehicle manufacturers. Rattle noises affect customer perception of vehicle quality. Rattle is an unwanted byproduct of clearances and is affected by design of the torsional system,including clutch spring,hysteresis and flywheel inertias and so on. By using a generic torsional drivetrain model for loaded gear rattle analysis,then,the nonlinear responses of the rattling gear is examined. The rattle of the 1 st gear set and 5 th gear set are considered while 2 nd gear is meshed and driven. The accelerations of the 5 th gear set are shown to be more severe under the same excitation condition and thus found to be a larger contributor to the rattle noise. The system is simulated by using a frequency sweep with engine excitation derived from measured data and then peak responses is examined.